SYNTHESIS OF COPPER OXIDE FROM COPPER SHEET AS HOLE TRANSPORTING MATERIAL IN PEROVSKITE BASED SOLAR CELL - MEDINA DEWI SARASWATI (NIM : 10212028), ELISABETH
Perovskite solar cells have attracted much attention from researchers because of its easy fabrication, inexpensive cost and it also has good. But one part of this perovskite solar cells, which is hole transport material (HTM), typically using a polymer material that is relatively expensive. Therefore, it is necessary to find another alternative materials that can serve as HTM but have a relatively less costly price and easy fabrication. One of alternative materials that can be used as HTM is copper oxide (CuO). CuO is a p-type inorganic semiconductor with monoclinic structure. CuO has a band gap that varies from 1.2 to 1.9 eV and high absorption coefficient. CuO can be synthesized simply from commercial copper using acetic acid and hydrogen peroxide to synthesize copper acetate precursor. Considering the abundance of copper in Indonesia and in order to make even less costly solar cell, then in this study CuO is made of commercial copper. CuO thin film is made using spin-coating method of copper acetate precursors on a substrate and then anneal it at temperature of 350 Ã‚Â°C. In this study, CuO thin film is succesfully synthesized from commercial copper sheet with spin-coating method. FTIR and EDS characterization shows that the synthesis of copper acetate is successfully done. The thickness of CuO thin film affects its transmittance and bandgap. The optimum concentration for copper acetate precursor is 0.2 M, because of its good transmittance, corresponding band gap and optimum conductivity. The optimum annealing temperature for CuO thin film is 350˚C. 2-propanol as solvent of copper acetate is better compared to ethylene glycol and water.